Smart Pet Feeder System and Big Data Processing to Predict Pet Food Shortage - et.al, M.K Razali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Focusing on pet owners who have tight daily schedule or physically disabled, this project proposed a smart pet feeder system with big data processing to predict pet’s food shortage. The project aims to help pet owners to regularly feed a correct amount of food to their pet as well as to predict the pet’s food shortage. The components used in this system are hx711 load cell amplifier, ultrasonic sensor, infrared sensor and servo motor. The ultrasonic sensor and the servo motor will be connected to adafruit, an internet of things (IoT) platform which provide online dashboard to allow pet owners to retrieve data from the sensors as well as to monitor the system activities. The online dashboard will also be connected to ifttt maker, another IoT platform to enable notifications via telegram. Pet owner will be notified via telegram every time the food is dispensed from the pet feeder system and if the pet food level is low. The system will dispense pet food automatically either at pre-set time or when pet comes near the pet feeder. More, the system can also collect data of pet food level to be used for time-series prediction on food shortage. Time-series prediction will use parallel processing method in handling big data for data pre-processing.